Malaysia-China defence ties: managing feud in the South China sea - Ngeow, Chow Bing (2022)
Notwithstanding the South China Sea dispute, there is support within the political and military leadership in Malaysia to develop and maintain defence cooperation with China. An unwritten mutual understanding seems to help both sides to contain their respective actions in the South China Sea within certain limits.